Rapid synthesis of MCM-41 and SBA-15 by microwave irradiation: promising adsorbents for CO2 adsorption - Oliveira, Marília R.; Cecilia-Buenestado, Juan Antonio; De Conto, Juliana F.; Egues, Silvia M.; Rodríguez-Castellón, Enrique (Elsevier, 2022)
It is known that the world scenario is one of constant search for sustainable technologies that can reduce the emission of carbon dioxide (CO2) in the atmosphere. This is because CO2 is seen as the main responsible for the increase in the generation of greenhouse gases, which leads to global warming and climate change. The development of efficient adsorbents for CO2 capture is a current challenge. MCM-41 and SBA-15 were synthesized in a microwave reactor and used as adsorbents in this work. Microwave irradiation presents itself as an easy synthesis strategy with less preparation time and energy requirement. The silica synthesis period was extremely reduced (1 h) at a temperature of 60 and 80 °C in the microwave reactor, obtaining silica with good textural and chemical properties. The CO2 adsorption isotherms were performed at 0, 25, and 40 °C at 1 bar. The MCM-41 and SBA-15 present favorable results for CO2 capture processes, showing that pure silica synthesized by microwave already obtains promising results, reaching a maximum adsorption capacity of 2.16 mmol g−1 (1 bar—0 °C) and a good fit for the Langmuir, DsL and Toth models. Furthermore, to increase CO2 adsorption, the mesoporous silica was also modified via impregnation with branched polyethylene diamine (PEI) or tetraethylenepentamine (TEPA). It is worth mentioning that microwave irradiation reduced the synthesis steps and improved the properties and adsorption capacity of the silica. This work opens new opportunities in the efficient preparation of materials that require optimizing the adsorbent synthesis process.
Keywords: Plantas -- Efectos del dióxido de carbono atmosférico; Microondas; Rapid synthesis; SBA-15; MCM-41; Microwave; CO2 adsorption